Baby corn production and utilization of remaining fodder in total mixed ration of buffalo calves - BAKSHI, M P S; WADHWA, M; KUMAR, BALWINDER (The Indian Journal of Animal Sciences, 2021)
This study was taken up to find out suitable maize variety cultivated with or without fertilizer for baby corn ear production and evaluation of leftover fodder/green stalks as livestock feed. Experiment-1: Six varieties of hybrid maize [PMH-1 grain (V1), Bulland (V2), African Tall (V4), Dekalb 7074 Monsanto (V5), Proagro 4640 (V6), Egyptian variety G-5414 (V7)] and one composite maize variety J1006 (V3) were cultivated without fertilizer (F1), with either Azotobacter treated seed (F2), recommended dose of fertilizer (F3), or F2 + F3 (F4) at the University Farm. Experiment-2: The leftover fodder of the best baby corn hybrid variety and that from V3 were evaluated in total mixed ration (TMR) as feed for buffalo calves. In Experiment-1 the weight of edible cob without husk and fodder yield were the highest (P<0.01) in V2. The in vitro net gas production, digestibility of nutrients and ME availability from the fodder was the highest in V7 comparable to V2, but higher than other varieties. The fodder from baby corn G-5414 was considered as the best. In Experiment-2 the chemical composition and in vitro evaluation of TMRs containing either conventional maize fodder (TMR-1; J-1006) or baby corn fodder (TMR-2; Baby corn G-5414) were comparable. Both the TMRs were iso-nitrogenous and iso-caloric. The digestibility of proximate and a cell wall constituent was considerably higher in calves fed TMR-2 than those fed TMR-1. The efficiency of nitrogen utilization, blood profile and excretion of purine derivatives in the urine were comparable in both groups. It was concluded that fresh baby corn fodder can be utilized efficiently by the ruminants without any adverse effect on the health of animals.